Effect of kumikata on grip strength and pinch strength of male university judoka - Kubo, J.; Kobayashi, K. (The Arts and Sciences of Judo, 2022)
Judo performance is strongly influenced by the technique and strength of the grip dispute. However, few studies have investigated these factors. The purpose of this study is to investigate the effect of the kumikata on the grip strength and pinch strength in male university judoka. The subjects of this study were 37 male university judoka. The grip strength and pinch strength of the judoka were measured. The latter was measured using a dedicated device with the first finger and the thumb as well as the third finger and the thumb. We also conducted a survey on the judo kumikata (right or left style). The grip strength of the tsurite was significantly higher than that of the hikite. The pinch strength between the third finger and the thumb of the tsurite was significantly higher than that of the hikite. The pinch strength between the first finger and the thumb was not significantly different between the tsurite and the hikite. It was shown that male university judo players have a higher grip strength for the tsurite than for the hikite and the pinch strength for the third finger and thumb is higher for the tsurite than for the hikite.